ANALISIS AKUNTANSI PENGAKUAN PENDAPATAN DAN BEBAN PADA PT PROPERTY GROUP IMPERIUM MEDAN - Santi Koeswara (EKSPOLHUM, 2024)
PT. Property Group Medan Empire is a company engaged in property. Real estate in a company can be declared competitive if it is in accordance with the development stage. The purpose of this research is to find out and analyze how accounting recognition of income and expenses on PT. Property Group Imperium Medan. This research uses descriptive method, namely the method of analyzing the problem by collecting data and grouping it in a sequence to describe each process, as well as the behavior of the object under study at PT. Property Group Imperium Medan so that it can provide objective information and information. The results of this study indicate that accounting for revenue recognition on PT. Property Group Imperium Medan was declared to be still incompatible with clear reporting transactions and in the principles and methods of sales in the calculation